2017
DOI: 10.1080/20008198.2017.1412225
|View full text |Cite
|
Sign up to set email alerts
|

Social support and posttraumatic growth in a longitudinal study of people living with HIV: the mediating role of positive affect

Abstract: Background: Psychological research in people living with HIV (PLWH) has been dominated by studies on the negative consequences of HIV infection. However, recently, positive changes following the diagnosis of HIV have been examined, namely the phenomenon of posttraumatic growth (PTG). Objectives: The aim of this one-year longitudinal study was to investigate the level of PTG and its relationship with social support dimensions (perceived support, need for support, actually received support) and positive and nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 65 publications
1
9
0
1
Order By: Relevance
“…Upon closer investigation, Relating to Others was the highest scoring PTGI factor, with New Possibilities as second. As a tendency to find meaning in facing this life-threatening disease, healthcare providers seem to change their sense of relationship, resulting in building closer bond with their family members and friends and a willingness to help others, as noted in other studies ( Khanjani et al, 2017 ; Rzeszutek, 2017 ; Tamiolaki and Kalaitzaki, 2020 ; Sun et al, 2021 ) when social support became an important source in coping with challenging events.…”
Section: Discussionmentioning
confidence: 90%
“…Upon closer investigation, Relating to Others was the highest scoring PTGI factor, with New Possibilities as second. As a tendency to find meaning in facing this life-threatening disease, healthcare providers seem to change their sense of relationship, resulting in building closer bond with their family members and friends and a willingness to help others, as noted in other studies ( Khanjani et al, 2017 ; Rzeszutek, 2017 ; Tamiolaki and Kalaitzaki, 2020 ; Sun et al, 2021 ) when social support became an important source in coping with challenging events.…”
Section: Discussionmentioning
confidence: 90%
“…Three studies revealed significant associations between higher education and PTG. Two reported a negative association between the two variables [75,65], and another indicated a stronger association between SWLS and PTG in less educated participants [68]. Some studies show possible adverse effects of higher education on PLWH's wellbeing, as education level may be associated with more intense perceived stigmatization (e.g., [86]).…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…A large body of research links social support to better mental health and lower odds of suicide among people living with HIV or other chronic illness (Bitew et al, 2016;Rzeszutek, 2017;Umberson and Montez, 2010). Higher social support (especially from caregivers) has been found to be protective against mental health difficulties among ALHIV (Gentz et al, 2017) and for suicidal behaviours among youth in high-income countries; this includes evidence from longitudinal studies (McKinnon et al, 2016;Teismann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%